GAMBARAN SANITASI LINGKUNGAN PADA STUNTING DI DESA SECANGGANG KABUPATEN LANGKAT - ANGGI PRASETYO; ROBITAH ASFUR (LP2MTBM MAKARIOZ, 2021)
Stunting is a linear plant abnormality of the child's body to be short or very short which is based on height according to agewith the threshold Z-score <-2 SD. Many factors that cause the condition of Stunting in the child causing the cause ofStunting missatunyayaitu environmental sanitation. To know the environmental sanitation Overview at stunting in the villageof District Secanggang Langkat. This type of research is descriptive with cross sectional design. The population of thisresearch is a child under the age of five in Secanggang village, Langkat Regency. The sampling technique in this study is atotal sampling. The data plan is taken with the height measurement and the filling of the observation sheet. The results of thisresearch conducted on stunting in the village of district Secanggang Langkat found most children 4 years old as many as 13people (48%), based on the gender of most women as much as 18 people (67%), based on Anthropometry most children inthe short category as much as 15 people (55%) And based on the sanitation level all in the category of unhealthy 27 people(100%). There is a picture of environmental sanitation in stunting in the village of District Secangganng Langkat.